Il Cortile delle Statue The Courtyard of the Statues - Giuseppe Cardone (Fuori Collana, 2018)
The celebration of the 794th anniversary of the founding of Federico II University represents the occasion to give back to the city one of its symbolic places, the Courtyard of the Statues in the Monumental Cloister of the House of the Savior. This architectural complex is famous for its sumptuous porch in Piperno stone, for the statues of the illustrious figures of the past, for the eighteenth-century sundials, for the great clock, finally restored today. Years of renovation work had prevented the full use of a building that for centuries has hosted one of the most extraordinary ancient book collections in Italy and that since the nineteenth century has been the scene of the intellectual development of generations of students. After the Unification of Italy a pantheon was created in the Monumental University Cloister with the statues of illustrious men of the past and present, to exhort new generations to the high values of ethics and scientific research. Choosing this venue to celebrate the foundation of one of the oldest universities in Europe means to collect the legacy of "an extraordinary past" in these complex times, as Gaetano Manfredi writes in his preface, "to highlight the beacon of critical thinking in the globalised growing from our strong historical roots".